PRELIMINARY STUDY ON THE IMPACT OF POLYMER-LIPID TYPES AND RATIO TO POLYMERIC-LIPID HYBRID NANOPARTICLE - PUSPITA, OKTAVIA EKA; WIDODO, FERRI; PUTRI, MONICA ANDIKA; ROSSARIZA, ISWA; FADHILLA, AVIOLA; SARI, NI PUTU JUNITA (International Journal of Applied Pharmaceutics, 2021)
Objective: This study aims to determine the best lipid to polymer ratios in polymeric-lipid nanoparticles using various types and ratios of polymers and lipids. Method: Polymeric-lipid nanoparticle was prepared using the modified one-step nanoprecipitation method. This study used chitosan and Na alginate as polymers and lecithin and egg phosphatidylcholine as lipids. The lipid was crossed-combined with polymer in various ratios, i. e 12.5%, 25.0%, and 37.5%. On its preparation, Cinnamomum burmanii extract was loaded into the resulted polymeric-lipid nanoparticle as an active substance model. The results were assessed its particle surface characteristics including particle size, polydispersity index, and zeta potential. Results: Twelve formulas resulted from crossed-combination between the lipid and polymer were used in this study. Polymeric-lipid nanoparticles resulted from the combination of egg phosphatidylcholine/Na alginate has particle size, polydispersity index, and zeta potential of 380.07±3.52 nm, 0.66±002, and-30.6±1.15 mV, respectively. Conclusions: The best lipid to polymer ratio and type was observed in egg phosphatidylcholine: Na alginate. The particle surface characteristics were better compared to other combinations.